2007
DOI: 10.1128/aem.01078-07
|View full text |Cite
|
Sign up to set email alerts
|

Rhizobacterial Volatiles Affect the Growth of Fungi and Arabidopsis thaliana

Abstract: Volatiles of Stenotrophomonas, Serratia, and Bacillus species inhibited mycelial growth of many fungi and Arabidopsis thaliana (40 to 98%), and volatiles of Pseudomonas species and Burkholderia cepacia retarded the growth to lesser extents. Aspergillus niger and Fusarium species were resistant, and B. cepacia and Staphylococcus epidermidis promoted the growth of Rhizoctonia solani and A. thaliana. Bacterial volatiles provide a new source of compounds with antibiotic and growth-promoting features.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
179
2
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 280 publications
(189 citation statements)
references
References 20 publications
6
179
2
2
Order By: Relevance
“…While both bacteria and fungi are capable of producing and consuming VOCs (Vespermann et al 2007;Wheatley et al 1997;Mackie and Wheatley 1999), we chose to focus our study on the response of the bacterial communities, as bacteria are particularly adept at consuming a range of VOCs (Bunge et al 2008;Mayrhofer et al 2006). Although previous work has shown that VOCs are capable of inhibiting and stimulating specific microbial taxa (Stotzky and Schenck 1976;Wheatley 2002;Mackie and Wheatley 1999;Tsuji et al 1990), the presence of litter VOCs to soils did not lead to appreciable changes in the relative abundances of individual bacterial taxa or overall bacterial community composition.…”
Section: Differences In Voc Emissions Across Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…While both bacteria and fungi are capable of producing and consuming VOCs (Vespermann et al 2007;Wheatley et al 1997;Mackie and Wheatley 1999), we chose to focus our study on the response of the bacterial communities, as bacteria are particularly adept at consuming a range of VOCs (Bunge et al 2008;Mayrhofer et al 2006). Although previous work has shown that VOCs are capable of inhibiting and stimulating specific microbial taxa (Stotzky and Schenck 1976;Wheatley 2002;Mackie and Wheatley 1999;Tsuji et al 1990), the presence of litter VOCs to soils did not lead to appreciable changes in the relative abundances of individual bacterial taxa or overall bacterial community composition.…”
Section: Differences In Voc Emissions Across Treatmentsmentioning
confidence: 99%
“…First, both Cleveland and Yavitt (1998) and Owen et al (2007) have demonstrated that consumption of specific VOCs in field soils result from microbial activities, not abiotic processes, such as sorption. Similarly, the growth of bacterial isolates in culture has been shown to be promoted by VOCs (Vespermann et al 2007;Mackie and Wheatley 1999) and the addition of VOCs to bulk soil directly increased CO 2 production (Amaral and Knowles 1997;Paavolainen et al 1998;Smolander et al 2006).…”
Section: Differences In Voc Emissions Across Treatmentsmentioning
confidence: 99%
“…Sensitivity to volatiles can strongly differ between fungal species and the extent of inhibition depends on the individual bacteria-fungus or fungus-fungus interaction (Kai et al, , 2009Vespermann et al, 2007;Garbeva et al, 2014b). Several independent studies have reported that F. solani is not much affected by bacterial volatiles, whereas Pythium species (oomycetes) are highly sensitive to bacterial volatiles (Kai et al, 2009;Effmert et al, 2012;Garbeva et al, 2014a,b).…”
Section: Volatile-mediated Antifungal Activitymentioning
confidence: 99%
“…Furthermore, exposure to bacterial volatiles has been reported to change fungal morphology, enzyme activity and gene expression (Wheatley, 2002;Vespermann et al, 2007;Minerdi et al, 2008Minerdi et al, , 2009Kai et al, 2009;Garbeva et al, 2011Garbeva et al, , 2014b. For example, activity of laccases and tyrosinases can be strongly affected by bacterial volatiles (Wheatley, 2002).…”
Section: Volatile-mediated Antifungal Activitymentioning
confidence: 99%
“…VOC with inhibitory effects on fungi, a phenomenon called fungistasis, is already known since the 70s (Hora & Baker, 1970, Hora & Baker, 1972, Lockwood, 1977. However, only in recent years, several studies paid renewed attention to the fungistatic effect of VOCs on spore germination and mycelial growth for a variety of fungi, including plant pathogenic fungi (Wheatley, 2002, Vespermann et al, 2007, Zou et al, 2007, Kai et al, 2009, Garbeva et al, 2011. Such VOCs with antifungal activity often include sulphur compounds, like dimethyl disulfide, dimethyl trisulfide, and S-methyl thioacetate and benzonitrile .…”
Section: Volatiles In Fungal-bacterial Interactionsmentioning
confidence: 99%